An Introduction to SABAH NATIVE LAW - Rooshida Merican Abdul Rahim Merican, author; Jady@Zaidi Hassim, author; Wan Syazana Akmal Wan Roslan, author; Hanani Azren Husin, author (Bangi : Penerbit Universiti Kebangsaan Malaysia, 2016)
Includes bibliographical references and index